2020
DOI: 10.1590/2238-38752020v10210
|View full text |Cite
|
Sign up to set email alerts
|

Urban Policies, Mobility and Gentrification in Two Neighbourhoods of Belo Horizonte 1

Abstract: This article investigates the relations between urban policies, the residential mobility and the gentrification of urban space, based on research in two neighbourhoods of Belo Horizonte: Santa Tereza and Anchieta. Several types of data were used in the study, including the Origin and Destination Survey, which identifies residential mobility in neighbourhoods, the Demographic Census datasets on households and residents, and municipal data on real estate dynamics and current urban policies. Qualitative data from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Nabuco et al (2017) showed the relevant participation of listed companies forming land banks in this region. A recent study was conducted on the gentrification of other neighbourhoods in Belo Horizonte, but it focuses on central area neighbourhoods (Andrade and Mendonça, 2020).…”
Section: Literature and Framework On Gentrificationmentioning
confidence: 99%
“…Nabuco et al (2017) showed the relevant participation of listed companies forming land banks in this region. A recent study was conducted on the gentrification of other neighbourhoods in Belo Horizonte, but it focuses on central area neighbourhoods (Andrade and Mendonça, 2020).…”
Section: Literature and Framework On Gentrificationmentioning
confidence: 99%